A Step-by-Step Procedure to Implement Discrete Choice Experiments in Qualtrics. (October 2021) - Weber, Sylvain
Discrete choice experiment (DCE) is a well-established technique to elicit stated preferences. It is frequently used in social sciences, where revealed preferences are difficult or sometimes even impossible to collect. A DCE consists in a series of choice tasks, in which survey respondents are requested to select the alternative they prefer among a few ones. Even though DCEs are conceptually well-known and documented, the practitioner may face technical issues once turning to their concrete implementation. This methodological note provides a step-by-step procedure to implement a DCE using the survey software Qualtrics. The procedure is largely automated, relying on the statistical software Stata and using HTML code to display the choice tasks in a pleasant way. Basic knowledge of Stata and HTML is desirable but not an absolute requirement. This note is intended to Qualtrics users, and prior knowledge of this survey tool is therefore assumed. A full working example with all codes and material is provided and presented.